Globalization : a calculus of inequality : perspectives from the South - Benn, Denis (Ian Randle Pub. KingstonJM, 2000)
Reflects a number of different philosophical and ideological perspectives on globalization and economic liberalization and the type of strategic responses that should be adopted by the developing countries in seeking to deal with the challenges posed by them.